A Narrative Review of Four Different New Techniques in Primary Anterior Cruciate Ligament Repair: "Back to the Future" or Another Trend? - Malahias, Michael-Alexander; Chytas, Dimitrios; Nakamura, Kaori; Raoulis, Vasileios; Yokota, Masashi; Nikolaou, Vasileios S (Sports Med Open, 2018)
Recently, four different operative techniques, referring to the primary anterior cruciate ligament (ACL) repair, were described. These are the dynamic intraligamentary stabilization (DIS) with Ligamys™, the Bridge-enhanced repair (BEAR), the use of internal brace, and the refixation with suture anchors. The purpose of this study was to assess the already-published, clinical, and pre-clinical results of those techniques. A literature review was conducted and implemented by three independent researchers. Inclusion criteria were clinical or cadaveric or animal studies about patients suffering from ACL rupture, who were treated with one of those four different arthroscopic techniques of primary ACL repair. There were 10 clinical trials dealing with the different techniques of primary ACL repair and 12 cadaveric or animal studies. The majority of the published clinical trials investigated the dynamic intraligamentary stabilization (DIS), while only four studies referred to the three other surgical techniques. Most of the clinical trials suggested that primary ACL repair should be done during the first 14-21 days after a proximal ACL rupture and not later. Further clinical evidence is needed for the techniques of bridge-enhanced ACL repair, internal brace, and suture anchors ACL refixation in order to support the animal and cadaveric biomechanical studies. Till now, the existing clinical trials were not enough to establish the use of those techniques in the ACL-ruptured patients. On the contrary, the Dynamic intraligamentary stabilization with Ligamys™ device demonstrated very promising results in different types of clinical studies.